Acute Approach to Central Nervous System Infections in Kazakhstan (Bangladesh Journal of Medical Science, 2024)
Background Neuroinfections in children are a socially significant problem of our time, as they can lead to disability and death of the patient, which actualizes the need for their early clinical diagnosis. The purpose of the study: to identify patterns of clinical manifestations of central nervous system lesions in children with neuroinfections. Materials and methods The cases of neuroinfections in 101 children treated at the “City Clinical Infectious Diseases Hospital” (Shymkent) in the period from 2018 to 2022 were analyzed, of which 37 patients with viral neuroinfections, 64 with bacterial ones. Results The predominance of bacterial neuroinfections over viral ones was revealed, with a predominance among young boys. Headache or its equivalents (in children under one year old) were observed in 72.5%; most often in children with viral infections of the nervous system (81.2%), less often in patients with bacterial infections (65.4%), p 0.01. In most cases, the disease manifested with the phenomena of fever and vomiting. When assessing the neurological status, the duration of preservation of two frequently occurring meningeal signs (rigidity of the occipital muscles, Kernig’s symptom) was taken into account, which was 6 ± 1.3 days and 5 ± 1.1 days in the group with bacterial neuroinfections, and 4 ± 1.8 and 5 ± 1.7 days, respectively, in the group with viral neuroinfections (p 0.05). With pneumococcal etiology, the most severe and protracted cases of the course of neuroinfections are recorded. Frequent emergency conditions in infectious lesions of the central nervous system in the form of cerebral edema, septic shock, which occur more often in bacterial neuroinfections, have been identified. Conclusion Neuroinfections are characterized by a symptom complex of clinical manifestations, which should be interpreted by doctors in a timely and correct manner in order to diagnose early and minimize adverse outcomes of the disease.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1206-1212